2014
DOI: 10.1007/s12024-014-9637-5
|View full text |Cite
|
Sign up to set email alerts
|

Sudden death due to biventricular non-compaction cardiomyopathy in a 14-year-old

Abstract: A 14-year-old African-American female with a long-standing medically and ablation-treated history of tachycardia with associated seizures died suddenly. Upon autopsy, evidence of gross non-compaction involving the left ventricle, as well as possible subtle non-compaction of the right ventricle was discovered. Microscopically, there was focal myocyte hypertrophy as well as myxoid connective tissue and subendocardial fibroelastosis in the areas affected by the non-compaction. Arrhythmia, precipitated by the unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 21 publications
0
6
0
2
Order By: Relevance
“…NCCM predominantly affects the left ventricle, both in children and adults. To date, few cases of biventricular noncompaction in children are reported [22][23][24][25][26][27]. Furthermore, in the left ventricle, NCCM predominantly affects the apex.…”
Section: Pathophysiologymentioning
confidence: 99%
“…NCCM predominantly affects the left ventricle, both in children and adults. To date, few cases of biventricular noncompaction in children are reported [22][23][24][25][26][27]. Furthermore, in the left ventricle, NCCM predominantly affects the apex.…”
Section: Pathophysiologymentioning
confidence: 99%
“…(8) Despite the fact that ILVNC is a congenital condition, it may present in adulthood. (5,(9)(10)(11) It is recommended that a meticulous three-generational family history be obtained to evaluate for genetic influence, as a positive family history has an impact on screening of other family members. (12) Follow-up of family members of an index case has identified a 30% familial occurrence.…”
Section: Casementioning
confidence: 99%
“…The prevalence of ILVNC is unknown, and echocardiographic studies have reported a prevalence of 0.014% -1.3%, (7,11) and the diagnosis may often be missed. A number of cases have been reported from Africa, (9,(22)(23)(24)(25)(26) including South Africa. (10,22) At a cardiomyopathy clinic in Johannesburg, the prevalence of ILVNC was 6.9%, and the diagnosis was based on echocardiographic criteria alone.…”
Section: Diagnosis Of Ilvncmentioning
confidence: 99%
“…Вовлечение в процесс обоих желудочков -редкое явление [5]. В зарубежной литературе есть единичные примеры бивентрикулярного некомпактного миокарда [6]. Описаны два случая сочетания бивентрикулярного некомпактного миокарда со снижением систолической и диастолической функции ЛЖ и легочной гипертензией [7,8].…”
unclassified